First report of Mesocriconema sphaerocephalum (Taylor, 1936) Loof, 1989 associated with carrot (Daucus carota subsp. Stativus) in Vietnam - Nguyen, Thi Duyen (J Nematol, 2019)
Our study recorded the presence of Mesocriconema sphaerocephalum on carrot in Hanoi city and Hai Duong province in Vietnam. This species was identified by morphometric, morphological characterizations, and molecular characterization of D2D3 of 28S rDNA sequence. To our knowledge, this is the first report of M. sphaerocephalum on carrot in Vietnam.